Identification and genetic characteristics of tusavirus in fecal samples of patients with chronic diseases in Guangzhou, China - He, Huan; Li, Yongzhi; Chen, Jiaqi; Xian, Juxian; Zheng, Liting; Sun, Hengbiao; Fan, Shunchang; Fu, Jiaqi; Li, Qiushuang; Chen, Caiyun; Liang, Minyi; Zhang, Minyi; et al. (Frontiers in Microbiology, 2023)
Purpose The Tunisian stool-associated parvovirus (Tusavirus (TuV)) is a novel member of the family Protoparvovirus, might be related to diarrhea. We investigated TuV prevalence in different populations and analyzed its genetic and bioinformatics features. Methods This study was conducted in a tertiary hospital in Guangzhou (China) from February 2018 to July 2022. Demographic and clinical information as well as stool samples were collected from individuals who visited the hospital. ProtScale, SwissModel, Datamonkey and other tools were used to analyze and predict the physicochemical parameters, tertiary structure, selection pressure, and B-cell epitopes of capsid viral protein 2 of the TuV (VP2-TuV) . Results A total of 3,837 participants were enrolled, out of whom two samples from patients with chronic illnesses tested positive for TuV DNA. However, no positive sample was detected in diarrhea group. Amplification of near-complete genome sequences was undertaken. Sequence alignment showed the homology between the TuV and parvoviruses from animals was higher than that of other parvoviruses from humans. Bioinformatics analysis revealed that VP2-TuV exhibited hydrophilic properties, and lacked transmembrane domains and signal peptides. The secondary structure of VP2-TuV was composed mainly of random coils and β-strands. Selective-pressure analysis of the VP2 region suggested that the TuV primarily underwent negative selection during evolution. Negatively selected codon sites coincided with residues comprising B-cell epitopes, suggesting minimal changes in the immunogenicity of the TuV over time. Conclusions The TuV was detected in patients with chronic diseases in China. The putative roles of the TuV in the pathogenicity of human diseases and zoonotic viruses must be determined by additional studies.